A distributed virtual presence system for the web. (30th May 2007) - Wolf, Heiner
This paper describes a Virtual Presence (VP) system for the web. A virtual presence is a chance for existing communities to extend their reach beyond the community website. But it can also create ad hoc and content-based communities. After a short history of VP systems, the paper enumerates requirements for large VP systems for the web. In addition to general requirements like scalability and privacy protection, the paper also explains more specific virtual presence-related requirements. A VP system for the web should have a flexible URL mapping and can be made protocol independent. The paper proposes a reference architecture for distributed VP systems and postulates design goals. The paper presents the LLuna system, and explains how LLuna meets the requirements. LLuna is a client-server system which shows users on web pages as avatars. It uses the Jabber network as transport and processing infrastructure.